1984
DOI: 10.1159/000118085
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of Diazepam and Propranolol in Patients with Panic Disorder and Agoraphobia

Abstract: The effects of oral doses of diazepam (single dose of 10 mg and a median dose of 30 mg/day for 2 weeks) and propranolol (single dose of 80 mg and a median dose of 240 mg/day for 2 weeks) on psychological performance of patients with panic disorders and agoraphobia were investigated in a double-blind, randomized and crossover design. Both drugs impaired immediate free recall but the decrease was greater for diazepam than propranolol. Delayed free recall was also impaired but the two drugs did not differ. Paiten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another study involving short-term chronic administration of diazepam failed to measure memory impairment several hours following the subject's previous dose (Ghoneim et al 1984a). A similar lack of correlation between the time course of memory impairment and the expected duration of plasma BZ levels has been noted in previous studies with drug-free subjects (Ghoneim et al 1984b;Kothary et al 1981 ;File and Bond 1979). We did not have the opportunity to determine whether the time course of memory impairment was altered by chronic BZ use.…”
Section: Discussionmentioning
confidence: 56%
“…Another study involving short-term chronic administration of diazepam failed to measure memory impairment several hours following the subject's previous dose (Ghoneim et al 1984a). A similar lack of correlation between the time course of memory impairment and the expected duration of plasma BZ levels has been noted in previous studies with drug-free subjects (Ghoneim et al 1984b;Kothary et al 1981 ;File and Bond 1979). We did not have the opportunity to determine whether the time course of memory impairment was altered by chronic BZ use.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, it has to be considered that some studies were performed in patients and others in healthy volunteers. For instance, Ghoneim et al (1984) found a deterioration in the free recall of a 24-word list after administration of propranolol (in doses from 80 to 320 mg) to patients with panic attacks and agoraphobia.…”
Section: Sleep Eegmentioning
confidence: 99%